Coulomb coupling effects in the gigahertz complex admittance of a quantum R–L circuit. (31st May 2018) - Song, L; Yin, J Z; Chen, S W
Abstract: We report on the gigahertz admittance measurements of a quantum conductor, i.e. a quantum R – L circuit, to probe the intrinsic dynamic of the conductor. The magnetic field dependence of the admittance phase provides us with an effective way to study the role of Coulomb interaction between counterpropagating edge channels. In addition, there is a small jump in the admittance phase when the transmitted modes are changed. This is because the gate voltage leads to a static potential shift of the quantum channel, then a quantum capacitance related to the density of states of the edge channels are influenced. Our study has made new discoveries of the dynamic transport in a quantum conductor, finding evidence for the deviations from quantum chiral transport associated with Coulomb interactions.